5x-11+9=x+2x

Simple and best practice solution for 5x-11+9=x+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-11+9=x+2x equation:


Simplifying
5x + -11 + 9 = x + 2x

Reorder the terms:
-11 + 9 + 5x = x + 2x

Combine like terms: -11 + 9 = -2
-2 + 5x = x + 2x

Combine like terms: x + 2x = 3x
-2 + 5x = 3x

Solving
-2 + 5x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-2 + 5x + -3x = 3x + -3x

Combine like terms: 5x + -3x = 2x
-2 + 2x = 3x + -3x

Combine like terms: 3x + -3x = 0
-2 + 2x = 0

Add '2' to each side of the equation.
-2 + 2 + 2x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 0 + 2
2x = 0 + 2

Combine like terms: 0 + 2 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| X^5+15x^3-16x=0 | | 1/2x+1/4x=4.5 | | -4x-9x=6(x+2)-(x+12) | | 7x+6+9x-6+8y-8+6y+1=360 | | (m-11)/7=-5 | | -2(j^2-k)-6(j^2+3k)= | | 4(-5x+8)=-168 | | 135=5m | | 8+9q=11+8q | | -2m+3(2m+1)=8m-9 | | 6(-3v+1)=5(-2-2) | | -(a+2b)+4(a-3b)-2(2a+b)= | | -3(2-x)=-39 | | -3/7x9/10 | | 28x+465=52x | | -6+5b=6b+7 | | -3+p/2=7 | | 3(9+x)=27 | | 3fourth+14=8 | | r^2(4r-8)=r-2 | | 5x+2y-9(8x-9y)= | | 6+7x=3x+6 | | 3x-5+5x-1=90 | | 18+4+x=9-19 | | 12=8n-4(6n-2) | | 4(3x+12)=6(2x+8) | | 9x^3+6x^2-24x=0 | | (-89)+(-40)+54-86= | | 10-2(4w-1)=60 | | 9u^2+24u-7=0 | | -x=73 | | 8+16-17-22= |

Equations solver categories